Selangor Public Library Corporation (PPAS) – Raja Tun Uda Library / Nursyafiqah Jamaludin ... [et al.] - Nursyafiqah, Jamaludin; Hazirah Syahirah, Hairuddin; Muhammad Syahrill, Kamaruzaman; Muhammad Danial, Yusman (2019)
This report is refer to Raja Tun Uda Library, Jalan Kelab Golf 13/6, Seksyen 13, 40100 Shah Alam, Selangor. The RATU is the headquarters of others 104 others libraries available in Selangor. The owner of the building is Sultan of Selangor, His Royal Highness the Sultan Sharafuddin Idris Shah Alhaj Ibni Sultan Salahuddin Abdul Aziz Shah Alhaj. The operation of RATU is handle by Selangor State Goverment. The library was developed by emulating edutainment concept (education + entertainment). This is because other than lending and reference services, the library also provides various services including Gymnasium, Bookshop, Seminar Room, Briefing Room, OKU Space, Cyber Zone, Mini 3D Theater, 6D Theater, Creative Zone, Reading Garden, Teenager’s Zone, Music Room, Adult’s Zone, Training Room and Hall. The library was build build beside the lake and surrounded by garden. This concept is adapted from Pustaka Sarawak. Raja Tun Uda Library also adopted the interior design of the building from Hong Kong Central Library. For example, the use of carpet in the building, the kid’s zone and others. The architecture of Raja Tun Uda Library is inspired from National Library Board, Singapore. For the shelving design, Raja Tun Uda Library adapted from Petronas Library.This report will explained about the all the system and management apply and this building.